On social inequalites on the pages of the Sociološki pregled / Sociological review in the period of self-management socialism - Jasmina, Petrović S; Marković Savić, Olivera S (Sociološki pregled, 2018)
It is quite possible to argue that sociology has acquired a large part of its scientifc legitimacy by studying social inequalities, and it can also be said that sociologists’ interest in their study was ofen mediated by the ideological mark of the community they belonged to, as well as other group and personal interests. The interest in acquiring a notion of the extent to which the sociological scientifc public of Serbia, according to the articles published in a relevant scientifc journal, was sensitive to the study of this problem is not conditioned solely by the awareness of the importance of the study itself. Our point of view is that sociology has ofen “sharpened” its critical potential by pointing to diﬀerent sources and outcomes of social inequalities in various domains of social life, giving unambiguous empirical evidence about them and oﬀering theoretical and methodological frameworks for their explanation and understanding. Tis has not only made it a relevant social science dealing with this universal phenomenon aﬀecting all societies that is increasingly being studied globally, but it enabled it to put the results of the research into the service of humane objectives of social development.The paper presents the results of an analysis of the contributions published in the Sociološki pregled/ Sociological Review relating to social inequalities, whether they are economic, political or cultural inequalities, as well as their consequences. The results of an elementary analysis of the thematic orientation and methods of processing the mentioned problems are presented with the aim to establish the scope and nature of scientists’ interest in this socially extremely important problem. The papers with explicit content belonging to the mentioned topic published in the aforementioned journal were analyzed, representating a relevant periodical in the feld of sociology in the Yugoslav area and the journal of the professional association of sociologists in Serbia.
Keywords: social inequality; poverty; social exclusion; Sociološki pregled/ Sociological Review; thematic focus